2023
DOI: 10.1002/adma.202302752
|View full text |Cite
|
Sign up to set email alerts
|

A Deformable Additive on Defects Passivation and Phase Segregation Inhibition Enables the Efficiency of Inverted Perovskite Solar Cells over 24%

Abstract: The defects and phase segregation in perovskite will significantly reduce the performance and stability of perovskite solar cells (PSCs). In this work, a deformable coumarin is employed as a multifunctional additive for formamidinium–cesium (FA‐Cs) perovskite. During the annealing process of perovskite, the partial decomposition of coumarin passivates the Pb2+, iodine, and organic cation defects. Additionally, coumarin can affect colloidal size distributions, resulting in relatively large grain size and good c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…The transient kinetics for the PEDOT:PSS sample, due to its lack of characteristic absorption around 450 nm in the ultraviolet–visible spectrum, are not applicable for this comparison. The PCP-2F–Li:POM sample’s GSB feature demonstrated slower decay rates compared to pristine CPE, suggesting improved hole transfer and diminished charge recombination, as indicated in ref . As depicted in Figure h, the integration of the PCP-2F–Li:POM layer led to a faster decay in the transient kinetics of the GSB signal for PM6, implying a more efficient hole transfer process to the PCP-2F–Li:POM HTL.…”
Section: Resultsmentioning
confidence: 99%
“…The transient kinetics for the PEDOT:PSS sample, due to its lack of characteristic absorption around 450 nm in the ultraviolet–visible spectrum, are not applicable for this comparison. The PCP-2F–Li:POM sample’s GSB feature demonstrated slower decay rates compared to pristine CPE, suggesting improved hole transfer and diminished charge recombination, as indicated in ref . As depicted in Figure h, the integration of the PCP-2F–Li:POM layer led to a faster decay in the transient kinetics of the GSB signal for PM6, implying a more efficient hole transfer process to the PCP-2F–Li:POM HTL.…”
Section: Resultsmentioning
confidence: 99%
“…25 The figure also presents the recovery kinetics of transient bleaching signals detected at 752 nm in the transient absorption (TA) spectra of both the reference and Ab-WPU modified perovskite films. 42–44 Fig. S9 (ESI†) illustrates the origin of the TA bleaching signal at 752 nm in the perovskite film, which stems from the band edge state filling of photoexcited charge carriers.…”
Section: Resultsmentioning
confidence: 99%
“…19 Xie et al utilized a deformable coumarin as an additive to passivate defects, regulated crystallization, and released residual stress, resulting in an excellent PCE of 23.13% in flexible PSCs. 20 Unfortunately, the weak interaction between these passivation materials and perovskite makes it difficult to continuously provide passivation effects and improve the moisture resistance of devices in an atmospheric environment. It has been found and reported that the strength of Pb−S bond is much greater than that of Pb−I bond, which promotes the development of many surface sulfidation strategies to construct stable and moisture-resistant perovskite surfaces.…”
Section: Introductionmentioning
confidence: 99%